Assessment of adult patients with chronic liver failure for liver transplantation in 2015: who and when?. Issue 4 (7th April 2016) - McCaughan, G. W.; Crawford, M.; Sandroussi, C.; Koorey, D. J.; Bowen, D. G.; Shackel, N. A.; Strasser, S. I.
Abstract : In 2015, there are a few absolute contraindications to liver transplantation. In adult patients, survival post‐liver transplant is excellent, with 1‐year survival rate >90% and 5‐year survival rates >80% and predicted median allograft survival beyond 20 years. Patients with a Child‐Turcotte Pugh score ≥9 or a model for end‐stage liver disease (MELD) score >15 should be referred for liver transplantation, with patients who have a MELD score >17 showing a 1‐year survival benefit with liver transplantation. A careful selection of hepatocellular cancer patients results in excellent outcomes, while consideration of extra‐hepatic disease (reversible vs irreversible) and social support structures are crucial to patient assessment. Alcoholic liver disease remains a challenge, and the potential to cure hepatitis C virus infection together with the emerging issue of non‐alcoholic fatty liver disease‐associated chronic liver failure will change the landscape of the who in the years ahead. The when will continue to be determined largely by the severity of liver disease based on the MELD score for the foreseeable future.